Specific therapy for transthyretin cardiac amyloidosis: a systematic literature review and evidence‐based recommendations - Marques, Nuno (2020)
Background The emergence of specific therapies for transthyretin cardiac amyloidosis (CA) warrants the need for a systematic review of the literature. Methods and Results A systematic review of the literature was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A systematic search was performed on MEDLINE, PubMed, and Embase databases on November 29, 2019. Studies were selected based on the following predefined eligibility criteria: English-language randomized controlled trials (RCTs), non-RCTs, or observational studies, which included adult patients with variant/wild-type transthyretin-CA, assessed specific therapies for transthyretin-CA, and reported cardiovascular outcomes. Relevant data were extracted to a predefined template. Quality assessment was based on National Institute for Health and Care Excellence recommendations (RCTs) or a checklist by Downs and Black (non-RCTs). From 1203 records, 24 publications were selected, describing 4 RCTs (6 publications) and 16 non-RCTs (18 publications). Tafamidis was shown to significantly improve all-cause mortality and cardiovascular hospitalizations and reduce worsening in 6-minute walk test, Kansas City Cardiomyopathy Questionnaire-Overall Summary score, and NT-proBNP (N-terminal pro-B-type natriuretic peptide) in variant/wild-type transthyretin-CA. Patisiran showed promising results in a subgroup analysis of patients with variant transthyretin-CA, which have to be confirmed in RCTs. Inotersen showed conflicting results on cardiac imaging parameters. The one study on AG10 had only a 1-month duration and cardiovascular end points were exploratory and limited to cardiac biomarkers. Limited evidence from noncomparative single-arm small non-RCTs existed for diflunisal, epigallocatechin-3-gallate (green tea extract), and doxycycline+tauroursodeoxycholic acid/ursodeoxycholic acid. Conclusions This systematic review of the literature supports the use of tafamidis in wild-type and variant transthyretin-CA. Novel therapeutic targets including transthyretin gene silencers are currently under investigation.